Preparation method of novel composite amniotic membrane lacrimal stent
By adopting a three-layer structure composite amniotic lacrimal tract stent, combined with polylactic acid-glycolic acid copolymer, amniotic powder, mussel protein and other materials, the problems of poor support effect and poor degradation of existing lacrimal stent biomaterials are solved. It achieves good support and healing effects, with excellent biocompatibility and degradability.
Patent Information
- Application Number
- CN202510025755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing lacrimal tract stents have problems such as poor support effect, single function, poor biocompatibility and degradability.
The composite amniotic lacrimal duct scaffold adopts a three-layer structure. The inner layer is a tubular composite inner core formed by polylactic acid-glycolic acid copolymer or mixture of its mixture is melt extruded, and the intermediate layer is amniotic powder, mussel protein, hyaluronic acid, The expansive sponge layer composed of chitosan, and the outer layer is a strengthened bioamniosome.
It achieves good drainage effect and support performance, provides appropriate expansion support capacity and drug loading capacity, promotes healing, reduces scars and inflammation, has good anti-degradation and mechanical properties, and avoids the risk of secondary surgery.
Smart Images

Figure CN119405914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a preparation method of a novel composite amniotic membrane lacrimal duct scaffold. Background Art
[0002] Tear duct obstruction is a common ophthalmic disease. It not only causes epiphora but also easily leads to secondary bacterial infection, causing acute and chronic dacryocystitis. Epiphora itself and the soaking of the face by tears are detrimental to beauty and cause physical and psychological discomfort to patients. Dacryocystitis, as an eye infection lesion, can spread to the eyeball and orbit, and is often a contraindication for intraocular surgery.
[0003] At present, the main methods for treating lacrimal duct obstruction are as follows: lacrimal duct irrigation and probing, dacryocystorhinostomy, lacrimal duct silicone intubation nasolacrimal duct stent, lacrimal sac removal, etc. Lacrimal duct irrigation and probing is simple and easy to perform, does not require expensive equipment, has a high recurrence rate in the treatment of lacrimal duct obstruction in adults, and is prone to cause endothelial damage, lacrimal puncta rupture, lacrimal canaliculus damage and false ducts. Currently, it is mainly used to treat congenital nasolacrimal duct obstruction. Dacryocystorhinostomy is a classic surgical method for treating lacrimal duct obstruction, including percutaneous, transnasal lacrimal nasal anastomosis, and transnasal endoscopic laser lacrimal cystorhinostomy. No matter which anastomosis method is used, the integrity of the nasal endothelial membrane and the normal anatomical and physiological structure of the lacrimal duct are destroyed. The early postoperative effect is ideal, but the bone hole is easily blocked by scabs and hyperplastic granulation tissue over time, resulting in surgical failure. In China, silicone tubes, artificial tubes or stents made of other materials are often used to treat lacrimal duct obstruction. The silicone tube material has good support resilience, but it cannot be degraded in the body, and requires secondary surgery to remove, causing secondary damage, and the effect is average. The above methods have a high short-term success rate, but a low long-term retention success rate. Some materials need to be removed by a second operation, and there is a risk of secondary damage to the tear duct. In order to avoid secondary damage, other degradable materials are often used to prepare tear duct stents. For example, stents made of polymers have good support effects, but lack the effect of promoting healing and are prone to scarring and inflammation during the recovery period. Lacrimal stents made of biomaterials have the effect of promoting healing and even resisting scarring and inflammation, but the support effect of the material is weak and cannot form a good channel dredging effect. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a novel composite amniotic membrane lacrimal duct stent, so as to solve the technical problems of poor biomaterial support effect, single function, poor biocompatibility and poor degradability existing in the existing lacrimal duct stent.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a novel composite amniotic membrane lacrimal duct stent, comprising a three-layer structure of an inner layer, a middle layer and an outer layer, wherein the inner layer is a tubular composite inner core formed by melt extrusion of polylactic acid-glycolic acid copolymer PLGA or a mixture of polylactic acid-glycolic acid copolymer and polycaprolactone into a hollow tube or woven with solid silk thread; the middle layer is an expanded sponge layer formed by a collagen solution containing one or more powders of amniotic membrane powder, mussel protein, hyaluronic acid, and chitosan, the expanded sponge layer is prepared into a columnar sponge layer by electrochemical deposition of collagen, and one or more components of anti-scar and anti-adhesion components of amniotic membrane powder, mussel protein viscosity material and chitosan anti-inflammatory component material are sprayed; the outer layer is prepared by strengthening treatment of biological amniotic membrane.
[0006] The preparation method of the novel composite amniotic membrane lacrimal duct stent specifically comprises the following steps: S1. The amniotic membrane is pretreated, chemically cross-linked and vacuum freeze-dried to obtain freeze-dried amniotic membrane, the freeze-dried amniotic membrane is cut into fixed sizes according to specifications to obtain an amniotic membrane coat, and the remaining freeze-dried amniotic membrane is freeze-crushed to obtain freeze-dried amniotic membrane powder; S2. Polylactic acid-co-glycolic acid (PLGA) or a mixture of polylactic acid-co-glycolic acid and polycaprolactone (PLGA / PCL) is melt-extruded and wound on a high-purity titanium cylindrical core to form a tubular structure; S3. The tubular structure prepared in step S2 and the high-purity titanium cylindrical core are used as the inner core and connected to the negative electrode of the power supply as the cathode, immersed in a collagen solution, connected to the positive electrode of the power supply with high-purity platinum as the anode, and powered on to electrochemically deposit collagen, so that the collagen is deposited on the high-purity titanium cylindrical core to obtain a collagen gel, and the collagen gel is cross-linked using an EDC / NHS solution to obtain a collagen scaffold; S4. freeze-drying the collagen scaffold in step S3 to obtain a scaffold collagen sponge layer; S5. The freeze-dried amniotic membrane powder in step S1 is mixed evenly with a viscous protein powder containing mussel protein or fibrin and an anti-inflammatory and healing-promoting powder containing hyaluronic acid or chitosan, and the mixture is evenly sprayed on the scaffold collagen sponge layer prepared in step S4 to obtain an initial collagen sponge layer scaffold; S6. placing the initial collagen sponge layer scaffold prepared in step S5 under a press to compress the sponge layer, then immersing the compressed initial collagen sponge layer scaffold in a mussel protein solution, wrapping one or more layers of amniotic membrane, and bonding and sealing the edges with a mussel protein solution, placing in a drying oven for low-temperature drying, and removing the high-purity titanium cylindrical core to obtain a composite amniotic membrane lacrimal duct scaffold; S7. After packaging, the composite amniotic membrane lacrimal duct stent is irradiated and sterilized, and then sealed and packaged for a second time.
[0007] Preferably, the pretreatment, chemical cross-linking strengthening and vacuum freeze-drying are specifically to wash with purified water, then remove the chorionic villus layer and residual blood stains of the amniotic membrane by blunt means, then activate and cross-link with a solution of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride and 2-morpholineethanesulfonic acid of N-hydroxysuccinimide, wash and vacuum freeze-dry to prepare freeze-dried amniotic membrane, and then cut to a suitable size to prepare the amniotic membrane coat.
[0008] Preferably, the ratio of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 1:1~5:1, the concentration of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride is 0.1mmol / L~1mmol / L; the concentration of 2-morpholineethanesulfonic acid is 0.05mol / L~1mol / L, the activation cross-linking temperature is 20°C~37°C, and the activation time is 3h~20h.
[0009] Preferably, the remaining freeze-dried amniotic membrane is placed in a low-temperature pulverizer for low-temperature pulverization and sieving, and freeze-dried amniotic membrane powder with a particle size between 100 μm and 300 μm is selected.
[0010] Preferably, in step S2, a polylactic acid-glycolic acid copolymer or a mixture of a polylactic acid-glycolic acid copolymer and polycaprolactone is placed in a melt extruder, and the equipment is started to extrude a polylactic acid-glycolic acid copolymer or a polylactic acid-glycolic acid copolymer and a mixture of polycaprolactone into a filament, wherein the ratio of the polylactic acid-glycolic acid copolymer to the polycaprolactone in the mixture is 1 to 10:1, the melt extrusion temperature is controlled between 160° C. and 220° C., and the diameter of the nozzle is controlled between 0.1 mm and 0.5 mm, to prepare a PLGA or PLGA / PCL mixture filament with a diameter of 0.1 mm to 0.5 mm.
[0011] Preferably, at least three strands of PLGA or PLGA / PCL mixture threads are taken and wrapped with a high-purity titanium cylindrical core with a diameter of 0.5 mm to 1 mm as a hard core, and a small amount of dichloromethane ethyl acetate solution is used as a bonding solvent at the connection points to weave the PLGA or PLGA / PCL mixture threads into a hollow cylindrical tube composite inner core with a diameter of 0.5 mm to 1 mm.
[0012] Preferably, in step S3, collagen is dissolved in acetic acid solution to prepare a 0.5% to 5% collagen acetic acid solution, the tubular structure and the high-purity titanium cylindrical core are immersed in the collagen acetic acid solution, the high-purity titanium cylindrical core is placed directly above the center of the collagen acetic acid solution, connected to the negative pole of the power supply, and the silk thread of the tubular structure is kept immersed in the collagen acetic acid solution, high-purity platinum is used as the anode to connect the positive pole of the power supply, and power is applied at a voltage of 15V to 30V for 10min to 30min to deposit the collagen on the high-purity titanium cylindrical core to form the collagen gel; the prepared collagen gel is placed at 2 The mixture is dried at 5°C to 37°C for 10 min to 30 min, and then transferred to an EDC / NHS solution for cross-linking at a temperature of 20°C to 37°C for 2h to 5h. The ratio of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide in the EDC / NHS solution is 1:1 to 5:1. The preparation method of the EDC / NHS solution is as follows: a phosphate buffer solution with a concentration of 0.1 mol / L to 0.4 mol / L is prepared, and EDC / NHS is weighed and dissolved in the phosphate buffer solution to obtain an EDC / NHS solution with a concentration of 0.1 mmol / L to 1 mmol / L.
[0013] Preferably, in step S6, the press is a pneumatic press having a circular groove with a diameter of 1.2 mm to 1.5 mm after the upper and lower pressing plates are combined. Under a pressure of 0.1 MPa to 0.5 MPa, the initial collagen sponge layer scaffold is compressed to form a uniform cylindrical shape with a diameter of 1.2 mm to 1.5 mm; the concentration of the mussel protein solution is 0.1% to 1%, and the amniotic membrane in step S1 is adhered to the initial collagen sponge layer scaffold to fix the amniotic membrane, and is placed at 30°C to 50°C for drying for 30 min to 120 min.
[0014] Preferably, in step S7, the composite amniotic membrane lacrimal duct stent is blister packaged, irradiated and sterilized, and then sealed and packaged again.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. A novel composite amniotic membrane lacrimal duct stent disclosed in the present invention comprises a three-layer structure of an inner layer, an intermediate layer and an outer layer, wherein the inner layer is a tubular composite inner core formed by melt extrusion of a polylactic acid-glycolic acid copolymer PLGA or a polylactic acid-glycolic acid copolymer and a polycaprolactone PLGA / PCL mixture into a hollow tube or solid silk thread, the intermediate layer is an expanded sponge layer formed by a collagen solution containing one or more powders of amniotic membrane powder, mussel protein, hyaluronic acid, and chitosan, the expanded sponge layer is prepared into a columnar sponge layer by electrochemical deposition of collagen, and one or more components of anti-scar and anti-adhesion components of amniotic membrane powder, mussel protein viscous materials, and chitosan anti-inflammatory component materials are sprayed; the outer layer is a biological amniotic membrane, which is prepared by strengthening treatment; the hollow mesh cylindrical structure is woven by melt extrusion of PLGA or PLGA / PCL mixture silk thread, compared with the existing lacrimal duct stent prepared from pure biological materials, it has a good drainage effect, and at the same time provides good support performance to maintain the patency of the channel; 2. The novel composite amniotic membrane lacrimal duct stent disclosed in the method of the present invention has suitable expansion support capacity and drug loading capacity. The sponge layer of the novel composite amniotic membrane lacrimal duct stent can expand by itself after absorbing liquid after compression, stably fix the material at the site to be repaired, and release the healing-promoting, anti-inflammatory, sticky protein, growth factor and other materials in the sponge layer, thereby accelerating repair and reducing the material's sensitivity to the body.
[0016] 3. The amniotic membrane outer layer of the composite amniotic membrane lacrimal duct scaffold prepared by the method of the present invention has good biological functions such as promoting mucosal repair and healing, reducing scar formation, reducing inflammation, and preventing adhesion.
[0017] 4. The composite amniotic membrane lacrimal duct scaffold prepared by the method of the present invention has suitable anti-degradation and mechanical properties. It forms a three-dimensional network structure through cross-linking of the amniotic membrane, thereby improving the mechanical properties of the amniotic membrane and enhancing its anti-protease degradation performance, thereby prolonging its in-place time after implantation in the body, and effectively ensuring that the lacrimal duct repair is completed before the material degrades.
[0018] 5. Compared with silicone materials, the composite amniotic membrane lacrimal duct stent prepared by the method of the present invention has good degradability. The composite amniotic membrane lacrimal duct stent is made of degradable materials as a whole, and only one operation is required, and no secondary removal is required. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the structure of the novel composite amniotic membrane lacrimal duct stent of the present invention; Figure 2 It is a schematic diagram of the cross-sectional structure of the novel composite amniotic membrane lacrimal duct stent of the present invention; Figure 3 It is a schematic diagram of the structure of the amniotic membrane outer layer of the novel composite amniotic membrane lacrimal duct stent of the present invention; Figure 4 It is a schematic diagram of the structure of the composite inner core of PLGA or PLGA / PCL mixture of the novel composite amniotic membrane lacrimal duct stent of the present invention; Figure 5 Schematic diagram of the electrode structure of the electrodeposition device in the preparation method of the novel composite amniotic membrane lacrimal duct stent of the present invention Figure 6 It is a schematic diagram of the structure of the composite inner core and sponge layer of the novel composite amniotic membrane lacrimal duct stent of the present invention; Figure 7 It is a schematic diagram of the structure of the composite inner core of the novel composite amniotic membrane lacrimal duct stent of the present invention after being assembled and wrapped with the amniotic membrane outer quilt; Figure 8 This is a physical picture of the novel composite lacrimal duct amniotic membrane scaffold in Example 2 of the present invention; Fig. 9 This is a diagram showing the dimensional changes of the novel composite lacrimal duct amniotic membrane stent before and after rehydration and swelling in Example 2 of the present invention; Fig.10 The CD31 expression diagram of rabbit lacrimal canaliculi at different time points in three groups of animal experiments in Example 3 of the present invention; Fig.11 This is a graph showing the expression of a-SMA in rabbit lacrimal canaliculi in three groups at different time points in the animal experiment in Example 3 of the present invention.
[0020] Reference numerals: 1 - outer layer; 2 - middle layer; 3 - inner layer. DETAILED DESCRIPTION
[0021] In order to make those skilled in the art better understand the technical scheme of the present invention, the present invention is further described in detail with specific embodiments in conjunction with the accompanying drawings, but it is not limited to a specific example, and this method can be applied to similar situations. In the embodiment, PLGA refers to polylactic acid-co-glycolic acid copolymer, and PLGA / PCL mixture refers to polylactic acid-co-glycolic acid copolymer and polycaprolactone mixture. In the following examples, the amniotic membrane is obtained by peeling off the placenta from cesarean section under sterile conditions after the parturient signs the informed consent form, and is a waste product separated from the living body. Example 1
[0022] See also Figures 1 to 7A novel composite amniotic membrane lacrimal duct stent comprises a three-layer structure of an inner layer 3, a middle layer 2 and an outer layer 1. The inner layer 3 is a tubular structure formed by melt extrusion of polylactic acid-glycolic acid copolymer PLGA or a mixture of polylactic acid-glycolic acid copolymer and polycaprolactone into a hollow tube or a solid silk thread; the middle layer 2 is an expanded sponge layer formed by a collagen solution containing one or more powders of amniotic membrane powder, mussel protein, hyaluronic acid, and chitosan. The expanded sponge layer is prepared into a columnar sponge layer by electrochemical deposition of collagen, and one or more components of anti-scar and anti-adhesion components of amniotic membrane powder, mussel protein viscous materials, and chitosan anti-inflammatory component materials are sprayed; the outer layer 1 is a biological amniotic membrane, which is prepared by strengthening treatment. The specific preparation method comprises the following steps: Step 1: Preparation of PLGA or PLGA / PCL mixture scaffolds: (1) Preparation of PLGA or PLGA / PCL mixture threads: A uniform mixture of PLGA or PLGA / PCL in a ratio of 1:1 was added to a melt extrusion device for melt extrusion, the extrusion temperature was set to 180° C., the extrusion port diameter was set to 0.5 mm, and the extruded PLGA or PLGA / PCL mixture threads were collected.
[0023] (2) Weaving of PLGA or PLGA / PCL hybrid scaffolds: See also Figure 4 A stainless high-purity titanium cylindrical core with a diameter of 0.8 mm was used as a stent, and multiple strands of silk thread were wound around the stainless high-purity titanium cylindrical core in a spiral form. An ethyl acetate solution with added dichloromethane was used as a bonding solvent at the connection points of the silk threads to prepare a spiral stent.
[0024] Step 2: Preparation of the outer layer of amniotic membrane: (1) Cleaning: Fresh amniotic membrane from healthy cesarean section should be washed 6 to 10 times with purified water, with no less than 500 ml of washing solution for 5 to 20 minutes each time, to fully remove the chorionic layer and blood impurities; (2) Cross-linking treatment: The washed amniotic membrane is cross-linked in an EDC / HNS MES solution, where the cross-linking buffer uses a 0.5 mol / l, pH 5.5 MES solution containing 0.5 mM EDC and 0.1 mM NHS solution, and cross-linked for 20 hours at room temperature. The cross-linked amniotic membrane is washed 5 to 10 times with purified water, each time with no less than 500 ml of washing solution, and each wash lasts 10 to 30 minutes. Ensure the safety of the material.
[0025] (3) Vacuum freeze drying: The cross-linked and washed amniotic membrane was spread flat in a vacuum freeze dryer for vacuum freeze drying.
[0026] (4) Cutting: See also Figure 3 The freeze-dried cross-linked amniotic membrane was cut into rectangular pieces according to the size requirements as the outer layer of the lacrimal duct stent. The remaining amniotic membrane material was placed in a ball mill at a speed of 1000 rpm / min, intermittently crushed, and the powder was sieved to retain the amniotic membrane powder with a particle size between 100 μm and 300 μm.
[0027] Step 3: Preparation of the middle sponge layer and assembly of the new composite lacrimal duct amniotic membrane scaffold: See also Figure 5 , assemble the electrodeposition device, take the PLGA or PLGA / PCL mixture containing high-purity titanium cylindrical core prepared in the above step 1 as the composite inner core, immerse it in 1% collagen acetic acid solution until the woven material is completely immersed in the collagen solution, connect the negative electrode of the power supply as the cathode, and use high-purity platinum as the anode to connect the positive electrode of the power supply, and also place it in the collagen solution, and keep it parallel to the cathode high-purity titanium and the distance is 1cm, set the power supply voltage to 20V, keep the power on for 30min, after the electrodeposition is completed, transfer the material on the high-purity titanium as a whole to a blast drying oven, dry it at 37°C for 15min, and then immerse it in 0.1mol / L PB buffer with a ratio of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide of 1:1 and a concentration of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride of 0.5mmol / L, the cross-linking temperature is 37°C, and the cross-linking is 3h. Then transfer to 500 ml purified water and rinse gently 5 times, 5 minutes each time, and then transfer to a vacuum freeze dryer for freeze drying to prepare the collagen sponge layer. For the structural diagram of the composite inner core and sponge layer, please refer to Figure 6 .
[0028] Take amniotic membrane powder, mussel protein powder, and chitosan powder and mix them evenly in a ratio of 20:10:3. After grinding and sieving, use spraying to evenly spray the powder on the above dried sponge layer. Place the scaffold material after spraying the material in a pneumatic press with a circular groove of 1.5 mm in diameter after the upper and lower pressing plates are combined. Under a pressure of 0.4 MPa, compress the material to form a uniform cylindrical material with a diameter of 1.5 mm.
[0029] Then apply 0.5% mussel protein solution to the longitudinal line at any position of the sponge layer, take the biological amniotic membrane cut to the size specification in step 2 and wrap it in a winding form, and finally apply 0.5% mussel protein solution to the amniotic membrane for bonding and fixing. Figure 7 Finally, the prepared composite lacrimal duct amniotic membrane scaffold is fixed in the packaging box for packaging and sealing.
[0030] Step 4: Sterilization of the new composite amniotic membrane lacrimal duct stent: The packaged new composite lacrimal duct amniotic membrane stent is sterilized by irradiation. Example 2
[0031] The expansion performance experiment of the composite lacrimal duct amniotic membrane scaffold prepared by the novel composite lacrimal duct amniotic membrane scaffold preparation method disclosed in the present invention, the actual picture of the composite lacrimal duct amniotic membrane scaffold can be seen in Figure 8 .
[0032] Experimental method: Take the new composite lacrimal duct amniotic membrane scaffold and place it in the test saline for rehydration, test the size of the product before and after swelling, and observe the expansion performance of the product.
[0033] Experimental results: The new composite lacrimal duct amniotic membrane stent in this embodiment was swollen with saline for 5 minutes and its dimensional changes were tested before and after. For the statistical results, please refer to Fig. 9 The initial average size is about 1.7 mm, and the average size after water absorption and swelling is about 2.1 mm, which proves that the composite lacrimal duct amniotic membrane scaffold prepared by the novel composite lacrimal duct amniotic membrane scaffold disclosed in the present invention has certain liquid absorption and swelling performance. Example 3
[0034] The composite lacrimal duct amniotic membrane scaffold prepared by the novel composite lacrimal duct amniotic membrane scaffold preparation method disclosed in the present invention is applied to an animal experiment on rabbit lacrimal duct injury.
[0035] Experimental methods: The above-mentioned new composite tear duct amniotic membrane scaffold was used for animal experiments, with the traditional silicone tear duct scaffold as the control group and the modeling group as the blank group. The rabbit lacrimal duct injury model was established by the lacrimal duct injection method of the sclerosing agent. The effect of the new composite tear duct amniotic membrane scaffold was determined by analyzing the CD31 and a-SMA index data in the damaged lacrimal duct tissue detected after surgery.
[0036] Experimental results: The experimental data of rabbit model animals in the modeling group, silicone group and amniotic membrane group were summarized and statistically analyzed.
[0037] CD31 is a major adhesion molecule of vascular endothelial cells. It is also expressed in vascular endothelial cells of the lacrimal canaliculi and is closely related to the proliferation of blood vessels. For the CD31 index in the animal experiment of this example, the modeling group expressed the most, followed by the silicone group, and the amniotic membrane group expressed the least. Please refer to Fig.10 .
[0038] a-Smooth actin (a-SMA) is expressed in canaliculus matrix myofibroblasts (MFB), reflecting the degree of canaliculus tissue fibrosis and participating in the central link of scar formation. In normal rabbit canaliculus tissue, a-SMA expression is negative. For the a-SMA index in the animal experiment of this example, the order of a-SMA average integrated optical density at each time point after surgery in the three groups is: modeling group>silicone group>amniotic membrane group, please refer to Fig.11 .
[0039] The expressions of CD31 and a-SMA in the injured rabbit lacrimal duct tissue were significantly increased. The lower the expression value, the closer it is to the expression value of normal rabbit lacrimal duct tissue, and the smaller the damage. From the experimental results, it can be seen that the new composite lacrimal duct amniotic membrane scaffold can reduce the inflammatory response, inhibit scar formation and inflammatory neovascularization in the healing process of rabbit lacrimal duct injury.
[0040] Of course, the above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by those skilled in the art within the essential scope of the present invention shall also fall within the protection scope of the present invention. The present invention does not elaborate on some of the known technologies of those skilled in the art.
Claims
1. A method for preparing a novel composite amniotic membrane lacrimal duct scaffold, characterized in that: The composite amniotic membrane lacrimal duct stent comprises a three-layer structure of an inner layer (3), an intermediate layer (2) and an outer layer (1), wherein the inner layer (3) is a tubular composite inner core formed by melt extrusion of polylactic acid-glycolic acid copolymer PLGA or a mixture of polylactic acid-glycolic acid copolymer and polycaprolactone into a hollow tube or woven with solid silk threads; the intermediate layer (2) is an expanded sponge layer formed by a collagen solution containing one or more powders of amniotic membrane powder, mussel protein, hyaluronic acid, and chitosan, wherein the expanded sponge layer is prepared into a columnar sponge layer by electrochemical deposition of collagen, and one or more components of anti-scar and anti-adhesion components of amniotic membrane powder, mussel protein adhesive material, and chitosan anti-inflammatory component material are sprayed; the outer layer (1) is biological amniotic membrane, which is prepared by strengthening treatment; The preparation method of the composite amniotic membrane lacrimal duct scaffold comprises the following steps: S1. The amniotic membrane is pretreated, chemically cross-linked and vacuum freeze-dried to obtain freeze-dried amniotic membrane, the freeze-dried amniotic membrane is cut into fixed sizes according to specifications to obtain an amniotic membrane coat, and the remaining freeze-dried amniotic membrane is freeze-crushed to obtain freeze-dried amniotic membrane powder; S2. Polylactic acid - glycolic acid copolymer PLGA or polylactic acid - glycolic acid copolymer and polycaprolactone PLGA / PCL mixture is melt-extruded and wound around a high-purity titanium cylindrical core to form a tubular structure; S3. The tubular structure prepared in step S2 and the high-purity titanium cylindrical core are used as the inner core and connected to the negative electrode of the power supply as the cathode, immersed in a collagen solution, connected to the positive electrode of the power supply with high-purity platinum as the anode, and powered on to electrochemically deposit collagen, so that the collagen is deposited on the high-purity titanium cylindrical core to obtain a collagen gel, and the collagen gel is cross-linked using an EDC / NHS solution to obtain a collagen scaffold; S4. freeze-drying the collagen scaffold in step S3 to obtain a scaffold collagen sponge layer; S5. The freeze-dried amniotic membrane powder in step S1 is mixed evenly with a viscous protein powder containing mussel protein or fibrin and an anti-inflammatory and healing-promoting powder containing hyaluronic acid or chitosan, and the mixture is evenly sprayed on the scaffold collagen sponge layer prepared in step S4 to obtain an initial collagen sponge layer scaffold; S6. placing the initial collagen sponge layer scaffold prepared in step S5 under a press to compress the sponge layer, then immersing the compressed initial collagen sponge layer scaffold in a mussel protein solution, wrapping one or more layers of amniotic membrane, and bonding and sealing the edges with a mussel protein solution, placing in a drying oven for low-temperature drying, and removing the high-purity titanium cylindrical core to obtain a composite amniotic membrane lacrimal duct scaffold; S7. After packaging, the composite amniotic membrane lacrimal duct stent is irradiated and sterilized, and then sealed and packaged for a second time.
2. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 1, characterized in that: The pretreatment, chemical cross-linking strengthening and vacuum freeze-drying specifically include washing with purified water, bluntly removing the chorionic villus layer and residual blood stains of the amniotic membrane, and then activating and cross-linking treatment with a solution of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride and 2-morpholineethanesulfonic acid of N-hydroxysuccinimide, washing and vacuum freeze-drying to prepare freeze-dried amniotic membrane, and then cutting into a suitable size to prepare the amniotic membrane coat.
3. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 2, characterized in that: The ratio of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 1:1-5:1, the concentration of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride is 0.1mmol / L-1mmol / L; the concentration of 2-morpholineethanesulfonic acid is 0.05mol / L-1mol / L, the activation cross-linking temperature is 20°C-37°C, and the activation time is 3h-20h.
4. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 2, characterized in that: The remaining freeze-dried amniotic membrane is placed in a low-temperature pulverizer for low-temperature pulverization and sieving, and freeze-dried amniotic membrane powder with a particle size between 100 μm and 300 μm is selected.
5. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 2, characterized in that: In the step S2, a polylactic acid-glycolic acid copolymer or a mixture of a polylactic acid-glycolic acid copolymer and polycaprolactone is placed in a melt extruder, the equipment is started, and the polylactic acid-glycolic acid copolymer or the polylactic acid-glycolic acid copolymer and polycaprolactone mixture is extruded into a silk thread, wherein the ratio of the polylactic acid-glycolic acid copolymer to the polycaprolactone in the mixture is 1 to 10:1, the melt extrusion temperature is controlled between 160° C. and 220° C., the diameter of the nozzle is controlled between 0.1 mm and 0.5 mm, and a PLGA or PLGA / PCL mixture silk thread with a diameter of 0.1 mm to 0.5 mm is prepared.
6. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 5, characterized in that: Take at least 3 strands of PLGA or PLGA / PCL mixture silk threads and wrap them around a high-purity titanium cylindrical core with a diameter of 0.5mm to 1mm as a hard core. Use a dichloromethane ethyl acetate solution as a bonding solvent at the connection point to weave the PLGA or PLGA / PCL mixture silk threads into a hollow cylindrical tube composite inner core with a diameter of 0.5mm to 1mm.
7. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 1, characterized in that: In the step S3, collagen is dissolved in acetic acid solution to prepare a 0.5% to 5% collagen acetic acid solution, the tubular structure and the high-purity titanium cylindrical core are immersed in the collagen acetic acid solution, the high-purity titanium cylindrical core is placed directly above the center of the collagen acetic acid solution, connected to the negative pole of the power supply, and the silk thread of the tubular structure is kept immersed in the collagen acetic acid solution, high-purity platinum is used as an anode to connect the positive pole of the power supply, and power is applied at a voltage of 15V to 30V for 10min to 30min to deposit collagen on the high-purity titanium cylindrical core to form the collagen gel; the prepared collagen gel is placed at 25°C to The mixture was dried at 37°C for 10-30 minutes, and then transferred to an EDC / NHS solution for cross-linking at a temperature of 20°C-37°C for 2-5 hours. The ratio of N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide in the EDC / NHS solution was 1:1-5:
1. The preparation method of the EDC / NHS solution was as follows: a phosphate buffer solution with a concentration of 0.1 mol / L-0.4 mol / L was prepared, and EDC / NHS was weighed and dissolved in the phosphate buffer solution to obtain an EDC / NHS solution with a concentration of 0.1 mmol / L-1 mmol / L.
8. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 1, characterized in that: In the step S6, the press is a pneumatic press with a circular groove with a diameter of 1.2mm to 1.5mm after the upper and lower pressing plates are combined. Under a pressure of 0.1MPa to 0.5MPa, the initial collagen sponge layer scaffold is compressed to form a uniform cylindrical shape with a diameter of 1.2mm to 1.5mm; the concentration of the mussel protein solution is 0.1% to 1%, and the amniotic membrane in the step S1 is adhered to the initial collagen sponge layer scaffold to fix the amniotic membrane, and is placed at 30℃ to 50℃ for drying for 30min to 120min.
9. The method for preparing the novel composite amniotic membrane lacrimal duct scaffold according to claim 1, characterized in that: In the step S7, the composite amniotic membrane lacrimal duct stent is packaged by blister packaging, sterilized by irradiation, and then sealed for a second time.
Citation Information
Patent Citations
Compound active amnion material, preparation method and application thereof and compound active amnion uterine cavity repair stent
CN103349798A
Novel degradable biological amniotic membrane composite lacrimal passage repair stent
CN104287877A
Regeneration and repair type lacrimal stent and preparation method thereof
CN108295313A
Degradable and foldable biological amnion composite repair stent
CN109394398A
Hydrogel lacrimal passage suppository and preparation method thereof
CN111773178A